An AHP enabled port selection multi-source decision support system and validation: insights from the ENIRISST project - Georgoulas, Dimitrios; Koliousis, Ioannis; Papadimitriou, Stratos (Springer, 2023)
Analytical Hierarchy Process (AHP) is a robust procedure for ranking options and supporting multi-criteria decision making that determine the port that a shipping operator will select, while designing the most cost-effective route. An important decision that may turn out to be decisive for a company’s survival. We developed an AHP based decision support system, as part of a wider Research and data Infrastructure system, that enables practitioners’ decision making based on their subjective experience and within realistic time constraints. We test the approach using two regional ports and the throughput results confirmed the initial expectations.
Keywords: AHP; Port selection; Decision support system; DSS; Greek ports